Non-Occlusive Small Bowel Necrosis in Association with Feeding Jejunostomy After Elective Upper Gastrointestinal Surgery - Spalding, Duncan RC (The Royal College of Surgeons of England, 2009)
INTRODUCTION: Non-occlusive small bowel necrosis (NOSBN) has been associated with early postoperative enteral feeding. The purpose of this study was to determine the incidence of this complication in an elective upper gastrointestinal (GI) surgical patient population and the influence of both patient selection and type of feeding jejunostomy (FJ) inserted, based on the experience of two surgical units in affiliated hospitals. PATIENTS AND METHODS: The records were reviewed of 524 consecutive patients who underwent elective upper GI operations with insertion of a FJ for benign or malignant disease between 1997 and 2006. One unit routinely inserted needle catheter jejunostomies (NCJ), whilst the other selectively inserted tube jejunostomies (TJ). RESULTS: Six cases of NOSBN were identified over 120 months in 524 patients (1.15%), with no difference in incidence between routine NCJ (n = 5; 1.16%) and selective TJ (n = 1; 1.06%). Median rate of feeding at time of diagnosis was 105 ml/h (range, 75–125 ml/h), and diagnosis was made at a median of 6 days (range, 4–18 days) postoperatively. All patients developed abdominal distension, hypotension and tachycardia in the 24 h before re-exploratory laparotomy. Five patients died and one patient survived. CONCLUSIONS: The understanding of the pathophysiology of NOSBN is still rudimentary; nevertheless, its 1% incidence in the present study does call into question its routine postoperative use especially in those at high risk with an open abdomen, planned repeat laparotomies or marked bowel oedema. Patients should be fully resuscitated before initiating any enteral feeding, and feeding should be interrupted if there is any evidence of feed intolerance.